IMPLEMENTATION OF BLUE ECONOMY PRINCIPLES IN WEAVING NUSANTARA TOURISM AND THE ROLE OF STATE-OWNED PORT ENTERPRISES AS CATALYSTS FOR THE GROWTH OF THE CRUISE SHIP TERMINAL AND MARINA INDUSTRY - K.P. Suharyono Soemarwoto Hadiningrat; Bahana Wiradanti; Yusuf Ferdian Umar (JIPOWER : Journal of Intellectual Power, 2024)
In October 2024, Indonesia begins a new chapter under the administration of President Prabowo and the Red and White cabinet. In this context, the author proposes the sustainable application of the Blue Economy Principles, with a special emphasis on the development of tourism and the creative economy as a strategic step to knit Nusantara Tourism. Support for the role of Port SOEs, especially Pelindo, is expected to function as a catalyst for the growth of the cruise ship terminal and marina industry. This paper will discuss the development of the Bali Maritime Tourism Hub as a model, as well as strategies to develop the cruise ship and marina-based tourism industry. The investment and development of cruise ship terminals and marinas by Pelindo in various regions of Indonesia has great potential to boost the regional economy and increase state revenue, so it is very important for the current government to provide maximum support to Pelindo. PT Pelabuhan Indonesia (Persero) or Pelindo as a state-owned enterprise engaged in port services in Indonesia has an important role in supporting economic growth through its role as a port manager and development. If sewing threads are analogous to maritime transportation, then strong threads are needed to weave fabric materials so that they are not easily torn. Kain can be anatomized as a region, for which efficient and reliable maritime transportation is the basic strength for the archipelago for economic development throughout Indonesia, increasing trade, tourism, and connectivity between regions. The Blue Economy is an economic development concept that utilizes resources from the sea wisely, sustainably, so that it can encourage economic growth at the same time while maintaining the marine ecosystem (United Nations, 2022). Within the scope of the Blue Economy, Indonesia not only has great potential in the marine and fisheries sectors, but also in renewable energy from the sea, maritime transportation and marine tourism.